Bargaining Power, Ownership, and Profitability of Transnational Corporations in Developing Countries - Lecraw, Donald J. (Journal of International Business Studies, 1984)
As the bargaining power of the transnational corporations (TNCs) in the sample increased relative to the bargaining power of the host country, and as the desire of the TNCs for a high level of equity ownership increased, the percent equity ownership of the TNCs in their subsidiaries increased. The relationship between percent equity ownership and subsidiary success from the TNCs' viewpoint, however, was J-shaped. High and low levels of equity ownership were associated with high levels of success. Control of critical operational variables by the TNC was directly related to success.